Optimal schedule of a dairy manufactory - Adonyi, R. (Array, 2009)
Summary: This paper deals with short-term scheduling of the dairy industry. Two different approaches are proposed for obtaining the minimal makespan schedules. According to the first, S-graph framework is proposed to find the optimal solution of the flow-shop scheduling problem. The problem is solved by applying the branch and bound technique. The second approach uses the integer programming formulation of the scheduling problem and BASIC genetic algorithm has been used to solve the optimization problem. Both approaches take into consideration volumes of units assigned to perform tasks, and respective size factors that affect the size of batches and their number must be produces to achieve production goals and thus on the schedules duration. Manufacturing of two type curds is used as a case study. The results obtained show that both approaches provide comparable solutions. Both approaches could be seen as a good alternative to project manager to find appropriate schedule of the dairy industry